Environmental and behavioral factors associated with household transmission of SARS-CoV-2 in children and adolescents - Oliveira, Faétila dos Santos; Guimarães, Rafael Alves; Afonso, Eliane Terezinha; Costa, Lusmaia Damaceno Camargo; Siqueira, Karina Machado; Marques, Solomar Martins; Rosso, Claci Fátima Weirich; Costa, Paulo Sérgio Sucasas da; Naghettini, Alessandra Vitorino; Barbosa, Maria Alves; Pagotto, Valéria; Aredes, Natália Del’ Angelo (Frontiers in Pediatrics, 2023)
Objective: To analyze the association between risk behaviors and environmental factors and SARS-CoV-2 infection in children and adolescents in the family environment. Methods: Cross-sectional and analytical study. A total of 267 children and adolescents aged 5-19 years who have contact with COVID-19-positive essential workers were tested between May and October 2020. Behavioral and environmental variables associated with SARS-CoV-2 infection were investigated. Association between these variables was performed using Poisson regression with robust variance. Results: The prevalence of positivity for SARS-CoV-2 was 25.1%. Following the confirmation of COVID-19 diagnosis of the index case, 92.1% of adults reported hand hygiene and 83.5% showed habits of respiratory etiquette. However, 12.7% wore masks in common areas of the residence before COVID-19. Sharing common objects was a risk factor for SARS-CoV-2 infection in the sample. Conclusion: Sharing objects among family members was identified as a risk factor associated with SARS-CoV-2 infection in children and adolescents who lived with infected adults. There was high frequency of hand hygiene and low prevalence of mask use.